Answer: [tex]x_1=6.73\\\\x_2=3.26[/tex]
Step-by-step explanation:
Given the following expression:
[tex](x-5)^2=3[/tex]
And knowing that:
[tex](a\±b)^2=a^2-2ab+b^2[/tex]
We get:
[tex]x^2-2(x)(5)+5^2=3\\\\x^2-10x+25=3[/tex]
Move the 3 to the left side of the equation:
[tex]x^2-10x+25-3=0\\\\x^2-10x+22=0[/tex]
Apply the Quadratic formula:
[tex]x=\frac{-b\±\sqrt{b^2-4ac} }{2a}[/tex]
In this case:
[tex]a=1\\b=-10\\c=22[/tex]
Substituting values into the Quadratic formula, we get:
[tex]x=\frac{-(-10)\±\sqrt{(-10)^2-4(1)(22)} }{2(1)}\\\\\\x_1=6.73\\\\x_2=3.26[/tex]